2008
DOI: 10.1093/jac/dkn307
|View full text |Cite
|
Sign up to set email alerts
|

A microbiological assessment of novel nitrofuranylamides as anti-tuberculosis agents

Abstract: Based on these studies, NFAs have many useful antimycobacterial properties applicable to TB chemotherapy and probably possess a unique mode of action that results in good activity against active and dormant M. tuberculosis. Therefore, the further development of lead compounds in this series is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 34 publications
7
81
0
Order By: Relevance
“…d PA-824-resistant mutant; a 400-bp deletion in fbiC is responsible for resistance, and complementation with wild-type fbiC restores susceptibility (19,25). e PA-824-resistant mutant; complementation with wild-type ddn restores susceptibility (19,25).…”
Section: T Deletion At Nucleotide Position 38 ͼ32mentioning
confidence: 99%
See 1 more Smart Citation
“…d PA-824-resistant mutant; a 400-bp deletion in fbiC is responsible for resistance, and complementation with wild-type fbiC restores susceptibility (19,25). e PA-824-resistant mutant; complementation with wild-type ddn restores susceptibility (19,25).…”
Section: T Deletion At Nucleotide Position 38 ͼ32mentioning
confidence: 99%
“…Moreover, we performed in silico modeling of the mutations in Fgd1 using the previously solved crystal structure of this protein (4). We included three PA-824-resistant positive controls (H37Rv-T3, H37Rv-5A1, and H37Rv-14A1) which had been previously analyzed genotypically and phenotypically (19,25).…”
mentioning
confidence: 99%
“…The effects of the analogs on exponentially growing S. aureus 8325 and membrane integrity were evaluated as described previously (11). Cytotoxicity was evaluated by exposing normal CCD-32Sk human skin fibroblast cells (ATCC, Manassas, VA) to antibiotics for 48 h, followed by an MTT [3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide] assay as described previously (8).…”
mentioning
confidence: 99%
“…With the same interest, the efficacy of anti-TB, 5-nitrofuranylamides NFAs (29a-e) against TB complex and other clinically relevant nonmycobacterial species [51] and found that the NFAs were significantly active against Mtb complex [52][53][54][55]. Compound 29a showed preeminent inhibition of MIC 0.006 mg/L against Mtb UT30 (streptomycin resistant at 4 mg/L).…”
Section: Piperazine and Pyrazine Derivativesmentioning
confidence: 96%